Whole-Genome and Transcriptome Sequencing-Based Characterization of Bacillus Cereus NR1 From Subtropical Marine Mangrove and Its Potential Role in Sulfur Metabolism - Kashif, Muhammad; Lu, Zhaomei; Sang, Yimeng; Yan, Bing; Shah, Syed Jalil; Khan, Sohail; Azhar Hussain, Muhammad; Tang, Hongzhen; Jiang, Chengjian (Frontiers in Microbiology, 2022)
Sulfur, organosulfur compounds, and sulfides are essential parts of life. Microbial sulfate assimilation is among the most active and ancient metabolic activities in the sulfur cycle that operates in various ecosystems. We analyzed the molecular basis of bacterial characterization. NR1 was isolated and purified from mangrove sediments. Whole-genome sequencing indicated that the NR1 isolate was closely related to Bacillus cereus. The genome contained 5,305 functional genes with a total length of 5,420,664 bp, a GC content of 35.62%, 42 rRNA, and 107 tRNA. DBT-grown cultures exhibited DBT utilization, fleeting emergence of DBT sulfone (DBTO2), and formation of 2-hydroxybiphenyl (2-HBP). Molecular analysis of the PCR products’ dsz operon revealed the presence of dszA, dszB, and dszC genes, which encoded for NR1’s 90% DBT desulfurization activity. Furthermore, 17 sulfur metabolism-related genes, including genes involved in assimilation sulfate reduction, APS and PAPS, and the cys, ssu, and TST gene families, were identified. In sulfate media, alkenesulfonate was converted to sulfite and inhibited ssu enzymes. Downregulated cysK variants were associated with nrnA expression and the regulation of L-cysteine synthesis. These findings established a scientific foundation for further research and application of bacteria to mangrove rehabilitation and ecological treatment by evaluating the bacterial characterization and sulfur degradation metabolic pathway. We used whole-genome and transcriptome sequencing to examine their genetic characteristics.